2022
DOI: 10.1021/acssuschemeng.2c00580
|View full text |Cite
|
Sign up to set email alerts
|

CO2 Fixation by Dual-Function Cu(triNHC) Catalysts as a Route to Carbonates and Carbamates via α-Alkylidene Carbonates

Abstract: This study employed dual-functional Cu­(triNHC) (triNHC = tri-N-heterocyclic carbene) catalysts for the efficient coupling of CO2 with alcohols and amines to form various carbonates and carbamates with good yields. The direct synthesis of carbonates and carbamates from CO2 was realized by the Cu­(triNHC)-catalyzed carboxylative cyclization of CO2 and propargyl alcohol and subsequent reactions with an additional nucleophile (alcohols or amines). The free carbene dangled from the Cu­(triNHC) catalysts deprotonat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 58 publications
0
13
0
Order By: Relevance
“…The next step was to evaluate the one-pot cascade reaction, which involves the formation of cyclic carbonates using CO 2 and propargylic alcohols, followed by nucleophilic attack by alcohols or amines to finally yield acyclic α-alkylidene carbonates. To the best of our knowledge, there is only one report using a copper catalyst . They reported the use of a Cu­(triNHC) complex to perform this cascade reaction.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The next step was to evaluate the one-pot cascade reaction, which involves the formation of cyclic carbonates using CO 2 and propargylic alcohols, followed by nucleophilic attack by alcohols or amines to finally yield acyclic α-alkylidene carbonates. To the best of our knowledge, there is only one report using a copper catalyst . They reported the use of a Cu­(triNHC) complex to perform this cascade reaction.…”
Section: Resultsmentioning
confidence: 99%
“…Intermediate IV subsequently reacted with CO 2 , leading to the formation of intermediate V . Finally, the cyclization was completed, resulting in the regeneration of the catalytically active [Cu­(NHC) 2 ] + species III . This mechanism highlights the multifunctional nature of the ionic liquid (IL) as it serves as a reservoir for carbenes, a CO 2 absorber, and solvent and eliminates the need for external bases, as the interaction between the IL and the alcohol activates the hydroxyl group.…”
Section: Resultsmentioning
confidence: 99%
“…Our research group has been interested in developing tri- N -heterocyclic carbene (triNHC)-coordinated metal complexes and sustainable catalytic reactions using them, where triNHC ligands provide unique steric and electronic effects to increase the stability and the catalytic properties in various organic reactions. It was reported that the catalytic activity for alcohol dehydrogenation was improved upon increasing the number of NHC ligands around the metal catalyst. , Unfortunately, we could not employ iridium complexes involving three NHC ligands for alcohol dehydrogenation because a triNHC-coordinated iridium complex was not formed under our previous synthetic conditions, in contrast to the facile formation of triNHC-coordinated copper and palladium complexes. , In this study, we report a new synthetic route forming tridentate NHC-coordinated iridium complexes and their improved activity (TOFs > 13,000 h –1 ) in hydrogen generation from EG (Scheme ). In addition to Ir­(triNHC)-induced rapid hydrogen production from EG, these catalysts also promoted C–C coupling of dehydrogenated EG to afford C n -α-hydroxy acids.…”
Section: Introductionmentioning
confidence: 99%
“…In a recent report, we described the synthesis of Cu(triNHC) (triNHC = tri-N-heterocyclic carbene) complexes and their use as catalysts in click chemistry and CO 2 conversion. 27,28 In this study, it is suggested that both the Cu ions and the dissociated NHC ligands in the Cu(triNHC) complex could facilitate the polymerization of glycidol with high tunability. The Cu ions coordinate with the oxygen in the epoxide, and the NHC ligand induces the deprotonation of the glycidol hydroxyl group, which initiates polymerization.…”
Section: Introductionmentioning
confidence: 99%
“…In our previous studies, it was found that Cu(triNHC) dissociates a carbene ligand to deprotonate the alcohol for the reaction. 28 Similarly, in this study, the reaction begins with the deprotonation of glycidol by the dissociated carbene ligand from the Cu catalyst. The proposed Cu complex having a protonated imidazolium group was observed by 1 H NMR of the reaction mixture (Fig.…”
mentioning
confidence: 99%